THE USE OF VIDEO METHOD TO IMPROVE STUDENTS’ WRITING ABILITY OF PROCEDURE TEXT AT THE EIGHTH GRADE STUDENTS OF SMP SATRYA BUDI PERDAGANGAN - Benarita; Riska Alfi Rahma (Program Studi Pendidikan Bahasa Inggris FKIP, 2021)
The objective of this research was to find out the effectiveness of using video method to Improve Students’ Writing Ability of Procedure Text at the Eighth Grade Students of SMP Satrya Budi Perdagangan. The design of this study was quantitative research where the writer using pre-test and post-test. The population of this research which consisted of three classes with total number 100 students where the writer will take the sample in VIII-1 which consist of 30 students. The data were obtained by using pre-test and post-test, the pre-test was given of the students before the treatment and the post-test was given after the treatment. The result of the research shows that the difference in writing ability between the students taught without video and the students taught by using video is very significant. There was increasing on the students’ ability in writing procedure text between pre-test and post-test. It showed with the pre-test data was 1487 and the mean 49,57 and after the treatment, post-test data was 2322 and the mean 77,4 and the result of standart deviation between pre-test and post-test was 34,53. So, Hypothesis Alternative (Ha) was accepted and Hypothesis Null (Ho) was rejected. It means that teaching by using video method in writing procedure text gave a significant increase toward students at SMP Satrya Budi Perdagangan